The Helicobacter pylori J99 jhp0106 Gene, under the Control of the CsrA/RpoN Regulatory System, Modulates Flagella Formation and Motility - Kao, Cheng-Yen; Chen, Jenn-Wei; Wang, Shuying; Sheu, Bor-Shyang; Wu, Jiunn-Jong (Frontiers in Microbiology, 2017)
CsrA has been shown to positively control the expression of flagella-related genes, including flaA and flaB, through regulating expression of an alternative sigma factor RpoN in Helicobacter pylori J99. Here, we aimed to characterize the CsrA regulatory system by comparative transcriptomic analysis carried out with RNA-seq on strain J99 and a csrA mutant. Fifty-three genes in the csrA mutant were found to be differentially expressed compared with the wild-type. Among CsrA-regulated genes, jhp0106, with unclear function, was found located downstream of flaB in the J99 genome. We hypothesized that flaB-jhp0106 is in an operon under the control of RpoN binding to the flaB promoter. The RT-qPCR results showed the expression of jhp0106 was decreased 76% and 92% in the csrA and rpoN mutants, respectively, compared to the wild-type. Moreover, mutations of the RpoN binding site in the flaB promoter region resulted in decreased expression of flaB and jhp0106 and deficient motility. Three-dimensional structure modelling results suggested that Jhp0106 was a glycosyltransferase. The role of jhp0106 in H. pylori was further investigated by constructing the jhp0106 mutant and revertant strains. A soft-agar motility assay and transmission electron microscope were used to determine the motility and flagellar structure of examined strains, and the results showed the loss of motility and flagellar structure in jhp0106 mutant J99. In conclusion, we found jhp0106, under the control of the CsrA/RpoN regulatory system, plays a critical role in H. pylori flagella formation.